Effect of adalimumab on sleep parameters in patients with psoriasis and obstructive sleep apnea: a randomized controlled trial. (February 2014) - Maari, Catherine; Bolduc, Chantal; Nigen, Simon; Marchessault, Philippe; Bissonnette, Robert
<x xml:space="preserve">Abstract</x> Introduction: Obstructive sleep apnea (OSA) is frequently seen in patients with psoriasis vulgaris. The effect of adalimumab, a TNF-α antagonist, on OSA is unknown. Methods: Patients with at least 5% of their body surface area covered with psoriasis and a sleep apnea defined as an apnea/hypopnea index (AHI) of at least 15 were recruited. They were randomized to either adalimumab 80 mg followed by adalimumab 40 mg every other week for 7 weeks or placebo. Patients were evaluated by polysomnography at baseline and day 56. The objective of this trial was to study the efficacy of adalimumab on sleep parameters in patients with psoriasis and OSA. The primary end point of this double-blind study was the change in AHI between baseline and day 56. Results: A total of 20 patients who were randomized completed the trial. There was no significant difference (p = 0.485) (95% CI = –21.07–42.73) at day 56 in the change from baseline in AHI between groups. Conclusions: Adalimumab used for 8 weeks at 40 mg every other week for the treatment of psoriasis did not improve OSA in this 20-patient study.